[PP.02.03] EFFICACY AND TOLERABILITY OF NIFEDIPINE GASTROINTESTINAL THERAPEUTIC SYTEM 60MG IN CHINESE PATIENTS WITH UNCONTROLLED HYPERTENSION. (September 2017) - Zhang, Y.; Liu, L.; Lu, F.; Zhao, Y.; Wu, Y.; Chen, L.; Sun, Y.; Yao, W.; Gao, P.; Chen, S.; Ji, X.; Mu, J.; et al.
Abstract : Objective: Efficacy and tolerability of nifedipine gastrointestinal therapeutic system (GITS) 60 mg once daily (QD) in uncontrolled blood pressure (BP) is not completely explored in China. Therefore, we studied the efficacy and tolerability of nifedipine GITS 60 mg in Chinese hypertensive patients inadequately controlled with prior monotherapy. Design and method: This single-arm phase-4 study (NCT02413515) enrolled 278 hypertensive adults from 13 centers in China, in whom BP was uncontrolled after 4-weeks of antihypertensive monotherapy. The patients received oral nifedipine GITS 60 mg QD for 8-consecutive weeks. Primary endpoint was mean sitting systolic BP control rate (MSSBP; <130 mmHg for subjects with diabetes (DM) and <140 mmHg for others) at 8-weeks. Secondary endpoints included change in MSSBP and mean sitting diastolic BP (MSDBP), 24-h SBP and DBP reduction measured by 24 hour ABPM, and safety of nifedipine GITS 60 mg. Results: A total of 269 patients (mean age 55 ± 8.21 years, 62.8% males, 28.3% with DM) were included for efficacy and 278 for safety analysis. At week 8, overall MSSBP control rate was 64.7%. From baseline to 8-weeks, decrease in MSSBP and MSDBP was −15.2 ± 11.37 mmHg (147.9 ± 6.87 mmHg to 132.7 ± 11.82 mmHg) and −6.4 ± 7.87 mmHg (89.1 ± 7.13 mmHg to 82.7 ± 8.04), respectively (Table 1). The control rate was lower in patients with DM From baseline to 8-weeks, mean 24-h SBP was decreased from 138.5 ± 12.78 mmHg to 131.6 ± 12.29 mmHg (diff. −6.9 ± 11.30 mmHg, 95% CI −8.29, −5.56) and mean 24-h DBP was decreased from 86.4 ± 9.32 mmHg to 82.5 ± 9.12 mmHg (diff. −3.9 ± 7.63 mmHg, 95% CI −9.47, −6.42). Fifty (18%) cases of adverse events (AEs) and 25 (9%) cases of peripheral edema were reported. No drug related serious AEs and deaths occurred during the study. Figure. No caption available. Conclusions: Nifedipine GITS 60 mg QD further improved control rate of MSSBP and MSDBP and was well tolerated in Chinese patients previously treated with standard dosage of antihypertensive monotherapy.